Harmonic components of finite amplitude sound waves reflected at a surface - FODA, M.A. (Archives of Acoustics, 2014)
The current analysis addresses the reflection of finite amplitude sound waves at a stationary surface. The analysis develops a two-orders perturbation solution for the nonlinear wave equation governing the velocity potential. The expression for the acoustic pressure derived from the potential lacked uniform validity. Hence it was corrected by employing coordinate straining transformations and thereby a uniformly accurate expression was obtained. Then, the strained coordinate transformations are eliminated by a Fourier analysis and a series representation solution is derived.